2020
DOI: 10.1093/jme/tjaa137
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High-Altitude Windborne Migration on Survival, Oviposition, and Blood-Feeding of the African Malaria Mosquito, Anopheles gambiae s.l. (Diptera: Culicidae)

Abstract: Recent results of high-altitude windborne mosquito migration raised questions about the viability of these mosquitoes despite ample evidence that many insect species, including other dipterans, have been known to migrate regularly over tens or hundreds of kilometers on high-altitude winds and retain their viability. To address these concerns, we subjected wild Anopheles gambiae s.l. Giles mosquitoes to a high-altitude survival assay, followed by oviposition (egg laying) and blood feeding assays. Despite carryi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Indeed, an outbreak of the mechanically transmitted myxomatosis (caused by Myxoma virus) was attributed to windborne mosquitoes flying from Australia to Woody Island, a distance of 320 km (Garrett-Jones, 1950). This observation adds to others in support of pathogens transmitted by windborne mosquitoes over long distances (Garrett-Jones, 1962; Sellers, 1980; Kay & Farrow, 2000; Reynolds et al ., 2006; Huestis et al ., 2019; Sanogo et al ., 2021). These results suggest that the key features of the few exceptionally widespread MBPs include transmission among people or domestic animals, as well as adaptation to at least one of the exceptionally widespread mosquito vectors, and often to other mosquito vectors that may be important to maintain the virus in sylvatic cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an outbreak of the mechanically transmitted myxomatosis (caused by Myxoma virus) was attributed to windborne mosquitoes flying from Australia to Woody Island, a distance of 320 km (Garrett-Jones, 1950). This observation adds to others in support of pathogens transmitted by windborne mosquitoes over long distances (Garrett-Jones, 1962; Sellers, 1980; Kay & Farrow, 2000; Reynolds et al ., 2006; Huestis et al ., 2019; Sanogo et al ., 2021). These results suggest that the key features of the few exceptionally widespread MBPs include transmission among people or domestic animals, as well as adaptation to at least one of the exceptionally widespread mosquito vectors, and often to other mosquito vectors that may be important to maintain the virus in sylvatic cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in land cover due to human settlement may also alter the temperature and increase mosquito migration to non-endemic high altitudes, for example in Kenya ( 67 ). One study showed that mosquitoes carried by wind continued surviving, breeding, and feeding on human blood, potentially expanding malaria transmission to new altitudes ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we hypothesize that wind may be an important factor for infected mosquito dispersion. There are several records of mosquitoes being carried considerable distances, as much as 177 km, by prevailing winds (Huestis et al, 2019;Sanogo et al, 2021).…”
Section: Landscape Connectivity Effects On Yellow Fever Virus Dispersionmentioning
confidence: 99%